Development and distribution of ancient landslides in the northwest corner of the Tibetan Plateau. Issue 5 (October 2021) - Wang, Wei; Huang, Yuandong; Xu, Chong; Li, Lei
Abstract: The periphery of the Tibetan Plateau is a landslide-prone area, yet there is a lack of satisfactory results on the development and distribution of landslides due to low human activity and inconvenient transportation within this area. In this study, taking 38–40°N and 73–76°E as the study region, a detailed distribution map of ancient landslides, including 5378 landslides with a total area of 2705.02 km 2, is established with the help of Google Earth Engine platform using manual visual interpretation. The numbers and areas of landslides, classified in terms of elevation, slope angle, slope aspect, fault distance, and water system distance, are analyzed. The development of landslides is closely correlated with topographical and geological factors. After comprehensive analysis, we conclude that both the number and total area of landslides in the elevation range of 4–5 km are the greatest; more landslides happen in the slope angle range of 40°–50°; the total area of landslides in the slope angle range of 50°–60° is the largest; both the number and total area of landslides with slope aspects of N, NE, and NW are the greatest; the ancient landslides in this region were weakly impacted by tectonic movement and seismic activity, and more likely caused by reasons like climate change; and the occurrence of ancient landslides in this region is insignificantly correlated with water systems.